Efektivitas Penerapan Model Problem Based Learning Terhadap Peningkatan Hasil Belajar Bola Voli - Budi Priyadi (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
This research is motivated by students who have difficulty solving basic service technical problems in volleyball learning. The 2013 curriculum recommendsapplying a learning model with a scientific approach. The purpose of this studywas to improve student learning outcomes in volleyball game material with basicservice techniques using a problem based learning (PBL) model. The methodused in this research is Classroom Action Research (CAR). The population is1025 students of MTs Negeri5 Kuningan, whilethe sample is 32 students ofclassIX.2.Thesamplingtechniqueispurposivesampling.Theresearchinstrument is volleyball service test. Analysis of research data using descriptivequantitativeanalysiswithms.Exceltofindouttheimprovementofserviceskillsin every cycle of Classroom Action Research. The results showed that applyingthePBLmodelcouldsignificantlyimprovethelearningoutcomesofvolleyball servicebasictechniques.Furtherresearchcanuseotherscientificlearningmodelsasacomparisonmaterialfortheeffectivenessofvolleyballlearningoutcomes